Uncovering the Molecular Mechanisms of Saurauia vulcani Korth in Rhodamine B Induced Colon Injury - Feimmy Ruth Pratiwi Sipahutar; Erlintan Sinaga; Masdiana Sinambela; Adriana Yulinda Dumaria LumbanGaol; Melati Nugrahalia Sipahutar (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The illegal food colorant, Rhodamine B (RhB), might lead to chronic colon injury. Saurauia vulcani is an ethnomedicine utilized for hepatoprotection, antioxidants, and immunomodulators. The histopathological and bioinformatic assays were conducted to discover the ethanolic extract of S. vulcani (EEP) against colon damage in RhB-induced rats. The abnormal results were exhibited in RhB administration, while EEP regained colon length and improved the histopathology of the ascending colon in rats. Furthermore, the construction of PPI predicted TP53, SRC, EGFR, AKT1, MTOR, CASP3, ABCG2, CTNNB1, MAPK14, MAPK8, and JUN as the main targets related to chronic colon injury. The molecular interaction presented S. vulcani had the stable fluctuation and strong binding affinities to thymidine phosphorylase. Therefore, this finding could be preliminary data for chronic colon injury treatment.